SuFEx Click: New Materials from SOxF and Silyl Ethers. Issue 46 (25th August 2016) - Yatvin, Jeremy; Brooks, Karson; Locklin, Jason
Abstract: New forms of click chemistry present new opportunities in materials science. Sulfur(VI) fluoride exchange (SuFEx) is a recently discovered click reaction between molecules containing SO x F groups and silyl ethers, two functionalities that are orthogonal to all other known click chemistries, that generates sulfate or sulfonate connections upon the addition of certain organobases or fluoride sources. SuFEx also has several important advantages over other click reactions in that it is insensitive to ambient oxygen and water, and its precursor materials, especially SO x F, are chemically, UV, and thermally inert. This Concept article focuses on the unique reactivity of SuFEx and its relation to building high molecular weight polymers and surface coatings, both of which make it a powerful new tool for materials science. Abstract : Sulfur(VI) fluoride exchange (SuFEx) is a newly discovered click reaction between molecules containing SO x F groups and silyl ethers that generates sulfate and sulfonate connections upon the addition of certain organobases or fluoride sources. This Concept focuses on the unique reactivity of SuFEx and its ability to build high molecular weight polymers and surface coatings, both of which make it a powerful new tool for materials science (see scheme).